2005
DOI: 10.3139/217.1873
|View full text |Cite
|
Sign up to set email alerts
|

Structure Development in Injection Molding: A 3D Simulation with a Differential Formulation of the Kinetic Equations

Abstract: A 3D Simulation with a Differential Formulation of the Kinetic EquationsThe purpose of the present work is to introduce a crystallization law into Rem3D, a 3D code written in C++ and dedicated to the injection molding of polymers. We kept the basic hypotheses of Avrami's model and cast the kinetic equations into a differential system that is solved numerically. The variation of the density of potential nuclei with temperature is taken into account. Furthermore, the distribution of mean spherulite sizes can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A differential form of this approach has been advanced by Patel and Spruiell [13]. An alternative to these models is the use of a system of differential "rate equations" [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A differential form of this approach has been advanced by Patel and Spruiell [13]. An alternative to these models is the use of a system of differential "rate equations" [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The growth rate of spherulites was described by the Hoffman-Lauritzen expression. [11] Smirnova et al [12] used a differential set of Avrami equations to predict crystallinity and the average size of spherulites in injection molding, but in their study only temperature effects were taken into account. In a different study, Pantani et al [13] investigated the effect of varying the packing pressure on the morphology of injection molded samples.…”
Section: Introductionmentioning
confidence: 99%
“…Since, we consider an Eulerian context, the position of the interface is treated as a scalar field, that is transported by the velocity field by solving an advection equation. In a previous paper (Smirnova et al , 2005a, b), a volume of fluid technique had been used to determine the flow front position, by transporting the volume fraction of filled polymer on each mesh element.…”
Section: Injection Molding Applicationmentioning
confidence: 99%
“…Knowing the temperature distribution at a certain instant, we solve crystallization kinetics, through the nonlinear system of equations: Equation 37 where: Equation 38 In the previous paper (Smirnova et al , 2005a, b), we have shown that Rem3D ® numerical resolution of this type of evolution problems was based on the space‐time finite discontinuous Galerkin finite element method. As for the temperature and the free surface, we have chosen to consider here a spatial continuous approximation.…”
Section: Injection Molding Applicationmentioning
confidence: 99%
See 1 more Smart Citation